ANALISIS KEMAMPUAN BERPIKIR REFLEKTIF SISWA SMA DITINJAU DARI GAYA KOGNITIF FIELD DEPENDENT DAN FIELD INDEPENDENT PADA MATERI BARISAN DAN DERET - Dwika Ananda Ayu Rahmawati S., - (2021)
Reflective thinking skill has an important role in solving mathematical problems. The ability to think reflective can be applied on topic sequences and series. Reflective cognitive style has a relationship to mathematical abilities and the ability of students to use concepts in questions. This study aims to analyze students' reflective thinking skills in terms of the field dependent and field independent cognitive styles on topic sequence and series material. The steps in this study were preparing field dependent and field independent cognitive style questionnaire, reflective thinking ability test, asking students to complete a questionnaire and take a test, and analyzing the results of the questionnaire and students' answers on the reflective thinking ability test. The subjects in this study were 6 students of class XI. The findings in this study indicate that students with a field independent cognitive style have better reflective thinking skills than students with a field dependent cognitive style. Students with field independent cognitive style were very good at connecting problems with the appropriate concept, while students with field dependent cognitive styles were not as good as field independent students in answering problems. The results of the analysis from the research can be used as material for consideration to make learning designs on the line and series material that are in accordance with the student's cognitive style.